Performance Indicators Analysis at Brazilian and Italian Women's Volleyball Leagues According to Game Location, Game Outcome, and Set Number. Issue 2 (April 2014) - Campos, Fabio A. D.; Stanganélli, Luiz C. R.; Pasquarelli, Bruno N.; Campos, Leandra C. B.; Gómez, Miguel-Ángel
This study was done to investigate the advantage of playing at home in elite women's volleyball leagues and the influence of performance indicators in the game score according to set number. The sample consisted of 240 games of the Brazilian Volleyball League ( n = 132 games) and the Italian Volleyball League ( n = 108 games) from the 2011–2012 season. The relationship of performance indicators (including serve, attack, block, and opponents' errors) with the game outcome (win or lose) was assessed. The results showed that there was a home advantage effect in women's volleyball leagues, with a higher prevalence of victory for the home teams in Brazilian and Italian leagues (58 and 56%, respectively). When related to the performance indicators and among the aspects that were most highly correlated with victory, the attack was the technical indicator that explained most of the results of volleyball games.